In vivo transplantation of neurosphere-like bodies derived from the human postnatal and adult enteric nervous system: a pilot study. - Susan Hetz; Ali Acikgoez; Ulrike Voss; Karen Nieber; Heidrun Holland; Cindy Hegewald; Holger Till; Roman Metzger; Marco Metzger (PLoS ONE)
Recent advances in the in vitro characterization of human adult enteric neural progenitor cells have opened new possibilities for cell-based therapies in gastrointestinal motility disorders. However, whether these cells are able to integrate within an in vivo gut environment is still unclear. In this study, we transplanted neural progenitor-containing neurosphere-like bodies (NLBs) in a mouse model of hypoganglionosis and analyzed cellular integration of NLB-derived cell types and functional improvement. NLBs were propagated from postnatal and adult human gut tissues. Cells were characterized by immunohistochemistry, quantitative PCR and subtelomere fluorescence in situ hybridization (FISH). For in vivo evaluation, the plexus of murine colon was damaged by the application of cationic surfactant benzalkonium chloride which was followed by the transplantation of NLBs in a fibrin matrix. After 4 weeks, grafted human cells were visualized by combined in situ hybridization (Alu) and immunohistochemistry (PGP9.5, GFAP, SMA). In addition, we determined nitric oxide synthase (NOS)-positive neurons and measured hypertrophic effects in the ENS and musculature. Contractility of treated guts was assessed in organ bath after electrical field stimulation. NLBs could be reproducibly generated without any signs of chromosomal alterations using subtelomere FISH. NLB-derived cells integrated within the host tissue and showed expected differentiated phenotypes i.e. enteric neurons, glia and smooth muscle-like cells following in vivo transplantation. Our data suggest biological effects of the transplanted NLB cells on tissue contractility, although robust statistical results could not be obtained due to the small sample size. Further, it is unclear, which of the NLB cell types including neural progenitors have direct restoring effects or, alternatively may act via 'bystander' mechanisms in vivo. Our findings provide further evidence that NLB transplantation can be considered as feasible tool to improve ENS function in a variety of gastrointestinal disorders.